STUDY OF DECISION FACTORS TO STAY IN HOTELS AND RESORT FOR THE GULF OF THAILAND’S WEST COAST - ปิ่นชุมพลแสง วีรวัลย์; จันทรโคลิกา กอบกูล (RMUTT Global Business and Economics Review, 2018)
This research aims to study the factors influencing decision making at Hotel and Resort of the Gulf of Thailand’s west coast by In-depth interviews with tourists whom want to stay. In the requests of guests in 3-star, 4-star and 5-star hotels, there was offered in qualitative research. The case study was used to collect data by interviewing in-depth interview. The main 24 informants were 26 to 50-year-olds. The results were: 1. In the opinion of hotel guests about hotel standards was the hotels which must be at the star level, according to the guest’s criteria. Considering with the hotel standard according to the concept of the Foundation Association for hotel standard consist of clean, convenient, international equivalent, full facilities and good security system according to the suitable of star standards. 2. The decision-making process found that the hotel quests want to stay at a 3-star, 4-star and 5-star hotel to determine by the star rating and facilities. The Characteristics of room were clean room and amenities according to star level of hotel standard. Star level of hoteling can to meet requirement better than every factors of hotel stay. In addition, the location of the hotel must mean that it is closer to the community center or near the beach. This location was the one factor to make the decision making process of hotel stay. The last factor affecting the hotel and resort stay of Thailand along the Gulf of Thailand coast was chain hotel and non-chain hotel to consider the international standard of hotel. If the chain hotel was faster than to make decisions for service standard of chain hotel then there had been create international standard of hotel. The factor of non-chain hotel must be determined by other factors, such as the star rating of the hotel, service process and feedback satisfaction from other customers. In addition, the new hotel will influence the decision to stay in this research. This factor made the decision to choose a hotel and resort along the Gulf of Thailand’s west coast to determine the willingness to pay hotel price.